El peculado menor resuelto como tráfico de influencias afecta a la seguridad jurídica en Ecuador - Valverde Landeta, Alexis Fernando (2018)
The embezzlement since the injury, the guardianship of public responsibility and fidelity for the fulfillment of state property, which must be proven in the trial, both the constituent elements, as well as the criminal liability and its harmful effects that are materially expressed in the quantum of the budgetary impact and of the violation of rights of the rights that is sought to solve through the budget, for what the damage was inflicted in the economic exercise of the occurrence of the crime and then it was prolonged in the constitution in last place for the fulfillment of these programs and projects that were affected and could not be executed as long as they did not occur and the sea: a) Payment of the repair b) The reprogramming and reallocation of funds for public participation for the fulfillment of rights, thus causing an affectation and not merely arithmetic. Depending on where the researcher sits, in the paradigm of guarantee or social control, minimum criminal law or maximum criminal law, is the treatment that should be given to the crime of embezzlement. From the perspective of social control, referring to crimes against public administration, which is where the crime of embezzlement is found in our legislation, these crimes protect the Public Administration, preserving the regularity of its functioning and the legality of administrative acts , which can be compromised by the arbitrary act in which the agent acts beyond its competence, by the omission of its necessary activity and by the illegal infringement of individuals in the sphere of competence of the Administration.